2019
DOI: 10.1016/j.chempr.2019.05.013
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Nanoscale Metal-Organic Framework Mediates Radical Therapy to Enhance Cancer Immunotherapy

Abstract: The authors report the use of nanoscale metal-organic framework (nMOF) to deliver Cu 2+ ions and porphyrins for estradiol-induced chemodynamic therapy and light-driven photodynamic therapy, respectively, to achieve local tumor control. The combination of nMOF-mediated radical therapy with anti-PD-L1 immunotherapy systemically rejects distant tumors via abscopal effects in a melanoma mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(140 citation statements)
references
References 70 publications
(65 reference statements)
2
135
0
Order By: Relevance
“…36,37 So, ICD inducers are classied into two categories: non-ER-targeting ones with collateral effects and ER-targeting ones with direct effects. 38 The non-ER-targeting category covers most of the currently known ICD inducers including chemotherapeutic agents, proteasome inhibitors, certain cell components and some non-ER-targeting PSs, 39,40 which is still not yet the ideal alternative due to the disequilibrium between the off-target effects and dose-limiting side effects. 41 It is in this context that ER-focused PDT is considered an ideal modality to t the criterion of ROS-based ER stress through the most simplied pathway.…”
Section: àmentioning
confidence: 99%
“…36,37 So, ICD inducers are classied into two categories: non-ER-targeting ones with collateral effects and ER-targeting ones with direct effects. 38 The non-ER-targeting category covers most of the currently known ICD inducers including chemotherapeutic agents, proteasome inhibitors, certain cell components and some non-ER-targeting PSs, 39,40 which is still not yet the ideal alternative due to the disequilibrium between the off-target effects and dose-limiting side effects. 41 It is in this context that ER-focused PDT is considered an ideal modality to t the criterion of ROS-based ER stress through the most simplied pathway.…”
Section: àmentioning
confidence: 99%
“…In view of that tumor hypoxia usually limits the efficiency of immunogenic photodynamic therapy, Lin and co‐workers proposed a new strategy by combining the Fe 3 O clusters and TBP ligand to construct Fe‐TBP NMOF‐based PS ( Figure a) . Fe 3 O catalyzed the production of oxygen to relieve hypoxia, TBP could be used to promote the conversion of oxygen to singlet oxygen, then the Fe‐TBP‐mediated PDT caused systemic anti‐tumor immunity, which could improve the αPD‐L1 immune checkpoint blockade for inducing the significant expression of cytotoxic T cells (CD 4+ and CD 8+ ). At last, the dual effect of infiltrating local and distant tumors was achieved.…”
Section: Tumor Therapymentioning
confidence: 99%
“…Subsequently, the same group developed cupric ion (Cu 2+ )‐based nMOF containing TBP, capable of catalyzing estradiol‐dependent ROS generation. [ 45 ] Studies have shown that estrogens can form stable adducts with DNA by generating ROS in the downstream metabolic processes that are catalyzed by bioavailable Cu 2+ ions. [ 46 ]…”
Section: Photodynamic Therapy and Its Immunomodulatory Effectmentioning
confidence: 99%
“…Ni and colleagues demonstrated that locally supplied Cu 2+ could hijack the estrogen metabolic pathways and promote cytotoxic superoxide and peroxide generation, whereas disassociated porphyrin can generate 1 O 2 through the PDT process. [ 45 ] They further showed the Cu 2+ ‐based nMOF, when combined with anti‐PD‐L1 antibodies, not only can induce an innate immune response but can also augment the tumor‐specific adaptive response, resulting in regression in both primary and distant tumors. [ 45 ]…”
Section: Photodynamic Therapy and Its Immunomodulatory Effectmentioning
confidence: 99%
See 1 more Smart Citation